STRUCTURE OF THE LAYERED INTERCALATE TAS2(CO(CP)(2))(0.25) - A POWDER X-RAY, NEUTRON-DIFFRACTION, AND SOLID-STATE NMR-STUDY - Evans, J; Ohare, D (1995)
In this paper the results of a structural investigation into the superconducting intercalate TaS2{Co(η-C5H5)2}0.25 are described. X-ray diffraction studies have revealed that the host layers are highly ordered in this compound and that intercalation is accompanied by a shift of adjacent TaS2 layers by √1/3 a along the [110] direction relative to their position in the pristine host lattice. Such a shift is driven by specific guest-host interactions. The X-ray structure has been refined by Rietveld profile analysis to RF = 6.7%; P3, a = 3.330(1), c = 23.040(8) Å. Variable-temperature neutron diffraction studies have been performed on TaS2-{Co(η-C5D5)2} 0.25 to investigate the guest molecules orientational preferences and dynamical properties. These neutron diffraction data suggest that the guest molecules' adopt an ordered superlattice and a single orientation with their principal molecular axis parallel to the host layers at all temperatures. Above approximately 280 K the molecules can undergo reorientation around the normal to the layers, but, on cooling, this motion is gradually frozen out, leading to the growth of additional reflections in the diffraction pattern.